CalciumZero: a toolbox for fluorescence calcium imaging on iPSC derived brain organoids - Xiaofu He; Yian Wang; Yutong Gao; Xuchen Wang; Zhixiong Sun; Huixiang Zhu; Kam W. Leong; Bin Xu (Brain Informatics)
Abstract Calcium plays an important role in regulating various neuronal activities in human brains. Investigating the dynamics of the calcium level in neurons is essential not just for understanding the pathophysiology of neuropsychiatric disorders but also as a quantitative gauge to evaluate the influence of drugs on neuron activities. Accessing human brain tissue to study neuron activities has historically been challenging due to ethical concerns. However, a significant breakthrough in the field has emerged with the advent of utilizing patient-derived human induced pluripotent stem cells (iPSCs) to culture neurons and develop brain organoids. This innovative approach provides a promising modeling system to overcome these critical obstacles. Many robust calcium imaging analysis tools have been developed for calcium activity analysis. However, most of the tools are designed for calcium signal detection only. There are limited choices for in-depth downstream applications, particularly in discerning differences between patient and normal calcium dynamics and their responses to drug treatment obtained from human iPSC-based models. Moreover, end-user researchers usually face a considerable challenge in mastering the entire analysis procedure and obtaining critical outputs due to the steep learning curve associated with these available tools. Therefore, we developed CalciumZero, a user-friendly toolbox to satisfy the unmet needs in calcium activity studies in human iPSC-based 3D-organoid/neurosphere models. CalciumZero includes a graphical user interface (GUI), which provides end-user iconic visualization and smooth adjustments on parameter tuning. It streamlines the entire analysis process, offering full automation with just one click after parameter optimization. In addition, it includes supplementary features to statistically evaluate the impact on disease etiology and the detection of drug candidate effects on calcium activities. These evaluations will enhance the analysis of imaging data obtained from patient iPSC-derived brain organoid/neurosphere models, providing a more comprehensive understanding of the results.